Analysis of the Implementation of the Minimum Service Standard Policy for Hypertension Patients at Katumbangan Community Health Centerpolewali Mandar District - Andini Yusroini,; Darmawansyah,; Muhammad Alwy Arifin,; Balqis,; Agus Bintara Birawida,; Healthy Hidayanti,; Anwar Mallongi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction:The health center as a first-level health facility functions as the front guard in supporting the achievement of the Minimum Service Standard target. The purpose of this study was to analyze the implementation of the minimum service standard policy for hypertension sufferers at the Katumbangan Health Center, Polewali Mandar Regency based on the theory of Donald Van Metter and Carl Van Horn. Method: This study used a qualitative method with a case study approach. The research informants consisted of 5 key informants and 2 additional informants using purposive sampling techniques . Results: This study shows that implementers have the same perception regarding the size and objectives of the policy . Human resources are not yet adequate in terms of quantity but are always developed through training in terms of quality. Service facilities are complete but there are no integrated health post buildings in each village and there is still a lack of funds. Information on this policy is conveyed through direct and indirect socialization, but it has not been evenly distributed to all targets. This policy has SOPs, duties and responsibilities of each agency as wellalready clearly fragmented. The social and economic environment of the community is less supportive, but the political conditions are quite supportive. Policy implementers also have a good response to implement this policy. Conclusion: The implementation of Minimum Service Standards for hypertension at the Katumbangan Health Center has been running quite well, but the Katumbangan Health Center needs to improve resources, communication to policy targets, and pay attention to the socio-economic conditions of the community.